Pemodelan Sistem Pendukung Keputusan Untuk Diagnosa Kesehatan Mental Dengan Metode Fuzzy Weighting Product - Nawindah Nawindah (Universitas Widyatama, 2022)
Mental health services are urgently needed after the Covid-19 pandemic, WHO stated that the mental health crisis that is happening in the world is increasing due to the Covid-19 pandemic. The impact on people's mental health is in the form of stress, anxiety, depression and trauma. so that an increase in the need for mental health services is needed. Health services at Budi Luhur University are available but have not used a decision support system with the fuzzy weighting product method in making an initial diagnosis. Given the limited number of counselors/psychologists compared to the number of students. For this reason, a decision support system model is needed to carry out an initial diagnosis of student mental health so that it can facilitate counselors/psychologists in conducting clinical services. The results of the study show that modeling a decision support system using the fuzzy weighting product method can be used to perform an initial diagnosis in recommending the mental health level of students.